The Congenital CMV infection - what we know about the symptoms, treatment and prevention? - Review of literature - Jaworska, Barbara; Pażyra, Aldona; Kusak, Natalia; Żak, Natalia; Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Kmiotek, Weronika; Oronowicz, Radosław; Ragan, Dagmara; Długosz, Joanna; Staszczak, Paweł (Quality in Sport, 2024)
Introduction: Cytomegalovirus (CMV) is a double-strand DNA virus, member of the viral family known as Herpesviridae which is wide-spread. CMV infection is the most common congenital infection worldwide. Disease is mostly asymptomatic for healthy people, therefore is detected late, when the children start presenting symptoms. Unfortunately the congenital CMV infection leads to the serious health problems for infants. Detection of the virus is typically done through quantitative PCR assays. Infection especially affects nervous system and can present infant’s deafness. Earlier it was equivalent with the children being deaf till the end of life, but nowadays thanks to the development of laryngological methods (ex. cochlear implantation) patients have chance to grow up correctly. Material and methods: A literature search was conducted using Google Scholar, PubMed, and Web of Science databases. We searched articles by entering key words in the appropriate configuration: “CMV”, “Congenital CMV infection”, “valganciclovir”, “infant’s deafness”. Scientific articles published between 1991–2023 were analyzed from all over the world and guidelines of Polish Society of Epidemiology and Infectious Diseases. Conclusions: Currently we haven’t got prevention towards congenital CMV, only the treatment for infants: valganciclovir. It stops development of severe symptoms. There are available analysis, where using valganciclovir during pregnancy reduces the possibility or soften the course of the congenital CMV infection , but it’s not the obligatory guidelines. In many countries researchers want to conduct screening test for CMV IgG among the pregnant women.